2023
DOI: 10.1530/jme-23-0017
|View full text |Cite
|
Sign up to set email alerts
|

A time- and space-resolved nuclear receptor atlas in mouse liver

Abstract: The functional versatility of the liver is paramount for organismal homeostasis. Adult liver functions are controlled by a tightly regulated transcription factor network including nuclear receptors (NRs), which orchestrate many aspects of hepatic physiology. NRs are transcription factors sensitive to extracellular cues such as hormones, lipids, xenobiotics etc. and are modulated by intracellular signaling pathways. While liver functional zonation and adaptability to fluctuating conditions rely on a sophistica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…PPARβ/δ is highly expressed in hepatocytes and nonparenchymal cells, including Kupffer cells (KCs), liver sinusoidal endothelial cells (LSECs) and hepatic stellate cells (HSCs) 31 . Our study indicated that PPARβ/δ affects the inflammatory response, and KCs are known to be the major effector cells of the inflammatory response in HIRI.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…PPARβ/δ is highly expressed in hepatocytes and nonparenchymal cells, including Kupffer cells (KCs), liver sinusoidal endothelial cells (LSECs) and hepatic stellate cells (HSCs) 31 . Our study indicated that PPARβ/δ affects the inflammatory response, and KCs are known to be the major effector cells of the inflammatory response in HIRI.…”
Section: Resultsmentioning
confidence: 76%
“…Previous studies have found that PPARβ/δ is highly expressed not only in hepatocytes but also in KCs. 31 We found that activation of PPARβ/δ reduced the expression of inflammatory cytokines in KCs. This will help to inhibit inflammation and apoptosis, ultimately alleviating HIRI.…”
Section: Discussionmentioning
confidence: 74%
“…102 In the liver, β-catenin regulates liver homeostasis, injury repair, and tumorigenesis, and protein expression is mainly found in pericentral hepatocytes. [103][104][105][106] While a relationship has been identified, the molecular mechanism of β-catenin and FXR interactions is undefined. In mouse models of hepatocellular carcinoma (HCC), FXR and β-catenin expression patterns display an inverse relationship.…”
Section: Beta Cateninmentioning
confidence: 99%
“…Taken together, these studies indicate that the FXR/ β-catenin complex inhibits hepatocyte FXR function, and due to peri-central protein expression pattern of β-catenin, exploration of interzonal and portal hepatocyte FXR should be further studied. 103,106 However, the formation of this complex may be transient, depending on injury caused by experimental cholestasis model, hepatocyte zonation, or ligand activation.…”
Section: Beta Cateninmentioning
confidence: 99%
“…12,16 However, the epithelial-damaging effects, underlying these pro-oncogenic properties, manifest at concentrations of bile acids > 100 µM while, at physiological intracellular concentrations (that are in the nano-micromolamolar range), bile acids are not cytotoxic and function as signalling molecules activating a family of cell membrane and nuclear receptors, known as bile acid-activated receptors, that maintains tissue and immune homeostasis. The Farnesoid-X-receptor (FXR), a receptor for primary bile acids 18 , and the G protein-coupled bile acid receptor 1 (GPBAR1) 20 , a receptor for secondary bile acids, are the two main bile acid sensors, functioning as integrative hubs between the intestinal microbiota and host metabolism and immunity 22 . Of relevance, FXR and GPBAR1 activation by natural and synthetic agonists 24,26 confers protection against colorectal cancers development, while their genetic ablation promotes entero-hepatic tumorigenesis in animal models 28,30,31 .…”
Section: Introductionmentioning
confidence: 99%